2013
DOI: 10.18632/oncotarget.1578
|View full text |Cite
|
Sign up to set email alerts
|

High aldehyde dehydrogenase activity identifies cancer stem cells in human cervical cancer

Abstract: High aldehyde dehydrogenase (ALDH) activity characterizes a subpopulation of cells with cancer stem cell (CSC) properties in several malignancies. To clarify whether ALDH can be used as a marker of cervical cancer stem cells (CCSCs), ALDHhigh and ALDHlow cells were sorted from 4 cervical cancer cell lines and 5 primary tumor xenografts and examined for CSC characteristics. Here, we demonstrate that cervical cancer cells with high ALDH activity fulfill the functional criteria for CSCs: (1) ALDHhigh cells, unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 48 publications
8
92
0
3
Order By: Relevance
“…Due to this high ALDH activity, these cells were sorted and injected subcutaneously ( s.c.) into nude mice. The in vivo assay demonstrated that cells with high ALDH activity (Table 1) are more tumorigenic compared to ALDH dim cells, as was also observed by the Liu group [36]. This data suggested that CCSC are present in the ALDH bright subpopulation, and it is a marker that can be used for target therapy.…”
Section: Discussionsupporting
confidence: 74%
“…Due to this high ALDH activity, these cells were sorted and injected subcutaneously ( s.c.) into nude mice. The in vivo assay demonstrated that cells with high ALDH activity (Table 1) are more tumorigenic compared to ALDH dim cells, as was also observed by the Liu group [36]. This data suggested that CCSC are present in the ALDH bright subpopulation, and it is a marker that can be used for target therapy.…”
Section: Discussionsupporting
confidence: 74%
“…5). After 48 h of seeding, >60% of adherent cells were ALDH1-positive and those percentages were reduced to ~30% upon reaching confluency, which are compatible with previous reports that the ALDH1-positive population in CaSki cells are 20-30% (32). In our experiments of Gremlin 1-exposure, the cells were ~60-70% confluent after 48 h of seeding (when we exposed cells to Gremlin 1) and became 90-100% confluent when assessed after 72 h of seeding.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, CD44-or CD133-positive cells are known to be more tumorigenic than negative ones in ovarian cancer (29,30). Similar findings have been suggested for side population (SP) cells in endometrial cancer and ALDH1-positive cells in cervical cancer (31)(32)(33)(34)(35)(36). Gremlin 1 is also reported to be expressed in cervical cancer compared to normal tissues of the cervix (37).…”
Section: Introductionsupporting
confidence: 63%
“…The ALDH enzymatic activity of the cells was measured as described previously (34), using the Aldefluor kit (StemCell Technologies, Vancouver, BC, Canada). CaSki cells (5x10 6 cells) were suspended in Aldefluor assay buffer containing ALDH substrate.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…In cervical cancer, ALDH1-positive cells, like other solid tumors, are known to be more tumorigenic than negative ones, and we used ALDH1 as a marker of cervical CSCs (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). First, using the cervical cancer cell line CaSki we confirmed that the expression of PAI-1 was significantly increased by changing coatings of culture plates as described (35), especially collagen IV-coating, confirmed by enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%